Analisis Pengaruh Layanan Paspor Online Terhadap Pengguna Dengan E-Govsqual - siti mona lisa (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The Immigration Office of Pekanbaru started providing online services on September 13, 2012, but there are still a few people who use these online passports because of difficulties in sending requirements because they often fail, information is not up to date, making it difficult to obtain information about the office, can open online passport links, and on the e-passport system there is no warning if any mistakes made by the applicant. Based on the above problem can be taken action analysis of the influence of online passport services to the community using e-govsqual dimension method. To know the significant relationship and influence between efficiency, trust, reliability, and community support for e-government. This study was tested by correlation and regression analysis assisted with SPSS application. The results show that efficiency variables 0.442, trust 0.269, reliability 0.141, community support 0.001 are related and have significant effect on e-government, efficiency, trust has the greatest influence, while reliability and community support have the least effect on e-government quality.